Analisis Isi Syair Adat “Maing Saing Lepo Toma Woga” Dalam Acara Pernikahan Di Desa Nita - Filipus Frid Lintu; Rimasi Rimasi; Robertus Adi Sarjono Owon (LPPM Politeknik Pratama, 2023)
The researcher's interest in the poem's substance and the significance of the traditional marriage poetry of maing saing lepo toma woga during a wedding ceremony in Nita Village, Sikka Regency, served as the inspiration for this study. The uncle's kid marriage system, the free marriage system, and the marriage system that is forbidden by custom are three significant divisions in the Sikka customary marriage system. The pronunciation of the traditional poem of Maing Saing Lepo Toma Woga, which is part of the wedding ritual, is a highly sacred component of the process of establishing a married bond. This is due to everyone's wishes and prayers for the bride.